Life under the sun - Ensminger, Peter A., 1957- (Yale University Press, 2001)
Which fungus is as sensitive to light as the human eye? What are the myths and facts about the ozone hole, tanning, skin cancer, and sunscreens? What is the effect of light on butterfly copulation? This entertaining collection of essays explores how various organisms - including archaebacteria, slime moulds, fungi, plants, insects, and humans - sense and respond to sunlight. The essays in Peter A. Ensminger's book cover vision, photosynthesis, and phototropism, as well as such unusual topics as the reason why light causes beer to develop a "skunky" odour. He introduces us to the kinds of eyes that have evolved in different animals, including those in a species of shrimp that is ostensibly eyeless; gives us a better appreciation of colour vision; explains how ploughing fields at night may be used to control weeds; and tells about variegate porphyria, a metabolic disease that makes people very sensitive to sunlight and may have afflicted King George III of England. These engaging essays present a complicated yet fascinating subject in an accessible way. The book will be treasured by anyone interested in the wonders of biology